KONTROVERSI PENGENAAN PAJAK PENGHASILAN ATAS TRANSAKSI VALUTA ASING - Solihin Makmur Alam (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
Article 4 section (1) Income Tax Law No. 17 / 2000 introduces what does the mean of Tax Objects. According to this article, Tax Objects shall be income, namely every kind of addition to economic capacity received or eamed by Taxpayers, derived both from Indonesia and outside Indonesia, which may be used for consumption or addition to property of the Taxpayers concerned, in whatever name or form.Income is the amount that a person can consume during a period of time and be as well-off at the end of the time as it was at the beginning. In other words, income is the amount that a person can be consumed without encroaching upon the capital.Moreover, income tax objects are very kind of addition to economic capacity, on the other hand, foreign exchane purchase transaction is an equity conversion in one form to another form which has the same value with it beginning equity. Thus, in this transaction , there is no addition to economic capacity received or earned by taxpayers. That's why, income tax deemed to foreign exchange purchase trasaction is not appropriate, because it will break the essence of source of law of income tax itself, that is income tax law No. 17/2000Keywords: Fiscal Stabilisation, tax object, Income, income tax deemed to foreign exchange purchase transaction.